Dementia and meaningful activity - Dening, Tom (2022)
Aim: This thesis presents nine of my published papers based around a common theme of meaningful activity in dementia. The papers and the accompanying text will explore the concept of meaningful activity and whether it is relevant to dementia; the use of meaningful activities for people living with dementia in various settings; and the experiences of people with dementia participating in such activities.